FAKTOR SOSIAL EKONOMI DAN PEMBERIAN ASI EKSKLUSIF TERHADAP STATUS GIZI BALITA UMUR 6-59 BULAN DI WILAYAH KERJA PUSKESMAS KEPATIHAN KABUPATEN GRESIK - Devi Lailatul Fitriah; Dwi Novri Supriatiningrum; Ernawati Ernawati (Universitas Muhammadiyah Gresik, 2023)
Socio-economic include education, employment, and income of parents. The implementation of exclusive breastfeeding in Gresik were was excellent and many mothers are aware of the importance of breastfeeding. The nutritional status of children was measured based on 3 indices, BB/U, PB/U, BB/PB. This study aimed toanalyze the relationship between socioeconomic status and exclusive breastfeeding with nutrition for children aged 6-59 monts. This study uses observational analysis with a cross-sectional conducted in the working area of the puskesmas in January - June 2022. With a sample of 148 toddlers, data analysis using the Spearman test and Lambda test. The results of the bivariate test showed that there was a socio-economic relationship with toddlers with nutritional status based on BB/U (p: 0.001), PB/U (p: 0.002), BB/PB (p: 0.003). For Lambda test results, it was found that there is a relationship between exclusive breastfeeding and the nutritional status of toddlers based on PB/U (p: 0.004) based on BB/U (0.009) but there is no relationship between exclusive breastfeeding and nutritional status of toddlers based on BB/PB (p: 0.705).